Mechanically Robust Free-Standing Single-Walled Carbon Nanotube Thin Films With Uniform Mesh-Structure by Blade Coating - Kato, Yuichi; Sekiguchi, Atsuko; Kobashi, Kazufumi; Sundaram, Rajyashree; Yamada, Takeo; Hata, Kenji (Frontiers in Materials, 2020)
Carbon nanotubes (CNTs) have garnered tremendous attention as building blocks for self-supporting membranes owing to remarkable developments in the manufacturing technology of high-quality CNT films. CNT films are expected to be applied in a wide range of applications, such as ultrafiltration membranes and as switching or sensing elements in micro electromechanical systems. However, the main challenge has been in fabricating CNT films by versatile and scalable processes suitable for industrial production retaining lab-scale high-performances. In this work, we succeed in fabricating macroscale (10-cm square) free-standing CNT films with thicknesses as low as 200 nm showing tensile strengths of ~ 166 MPa by simple, versatile, and scalable blade-coating of CNT suspensions. Our study demonstrates that it is possible to control CNT film bundle size distribution and pore structure by controlling the CNT dispersibility and entanglement in the suspensions. We find that controlling bundle size distribution, pore structure uniformity and packing can lead to 5-fold, 4-fold and 3-fold higher tensile strengths, fracture strain and Young’s modulus, respectively compared to films with poorer uniformity and packing.